Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/5073625
|View full text |Cite
|
Sign up to set email alerts
|

Easy Access to Biomedicine and Knowledge about Medicinal Plants: A Case Study in a Semiarid Region of Brazil

Abstract: We aimed to evaluate how proximity to urban areas interferes with the relationship between socioeconomic variables and various aspects of medicinal plant knowledge. The study was conducted in six communities of the Catimbau National Park (PARNA Catimbau) in the state of Pernambuco. Eighty participants were interviewed. The communities were divided into two groups according to their distance from the nearest urban center. Socioeconomic data and information on medicinal plants were collected through semistructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Hence, medicinal plants are vital for treating ailments in these communities. Several previous investigations carried out in this area (Laurentino et al 2022, Reinaldo et al 2020, Silva et al 2021, Sousa et al 2022a have highlighted the relevance of medicinal plants in the health care of this locality.…”
Section: Study Areamentioning
confidence: 90%
See 1 more Smart Citation
“…Hence, medicinal plants are vital for treating ailments in these communities. Several previous investigations carried out in this area (Laurentino et al 2022, Reinaldo et al 2020, Silva et al 2021, Sousa et al 2022a have highlighted the relevance of medicinal plants in the health care of this locality.…”
Section: Study Areamentioning
confidence: 90%
“…In previous studies conducted by our research team in these communities, we observed that the informants had low levels of education and were engaged in professional occupations related mainly to subsistence agriculture (Magalhães et al 2021;Sousa et al 2022a,b). Additionally, there is a significant reliance on natural resources for disease treatment since access to the public health system is restricted (Reinaldo et al 2020, Sousa et al 2022a. Healthcare facilities are situated in a minor village outside the PARNA Catimbau, known as Vila do Catimbau; these facilities are approximately 15 km away from these communities and accessible via dirt roads.…”
Section: Study Areamentioning
confidence: 99%
“…Additionally, the Lagoa do Junco Community is characterized by a strong tradition of using and commercializing medicinal plants (Dantas et al 2020, Pereira et al 2021. Furthermore, community members possess significant expertise in medicinal plants and often have lower incomes, a common situation in other areas of Northeast Brazil (Magalhães et al 2022, Sousa et al 2022, Oliveira et al 2017, which is why they frequently resort to medicinal plants to address their health concerns. The strong history of using and selling medicinal plants prompted us to select this community for our study.…”
Section: Study Areamentioning
confidence: 99%
“…Without claiming that species knowledge is more developed in the animal kingdom, zoocentrism and plant blindness (Wandersee and Schussler, 1999;Frisch et al, 2010) poses a mayor problem to plant conservation (Balding and Williams, 2016). However, peer reviewed studies on environmental education using medicinal plants are scarce 1 (though see Azevedo et al, 2015;Staniszewski et al, 2016) and, case studies in the Global South report a discrepancy between knowledge and use of medicinal plants, a decrease in the knowledge with increasing formal educational and an inter-generational erosion of knowledge (Srithi et al, 2009;de Sousa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%